Pengaruh Sistem Pengendalian Internal Terhadap Penerapan Sistem Komputerisasi Haji Terpadu (SISKOHAT): Studi Pada Kantor Kementerian Agama Kabupaten Bengkalis - Wahyu Syintia Putri; Decky Hendarsyah (Inovbiz: Jurnal Inovasi Bisnis, 2020)
This research aims to examine whether the Internal Control System affects the application of the Integrated Hajj Computerized System at the Office of the Ministry of Religion in Bengkalis Regency. The sample in this study amounted to 54 respondents from all employees in the Bengkalis Regency Ministry of Religion office. The type of data used in this study is a quantitative approach. Data collection techniques used were interviews, questionnaires, documentation, literature study and observation. While the data analysis technique used is to use simple linear regression analysis. After conducting research it was found that significantly the Internal Control System affected the application of the Integrated Hajj Computerized System in the office of the Ministry of Religion in Bengkalis Regency.